A Study of Aerobic Photooxidation with a Continuous-Flow Microreactor - Nagasawa, Yoshitomo; Tanba, Katsuya; Tada, Norihiro; Yamaguchi, Eiji; Itoh, Akichika (Synlett, 2015)
We report the development of an aerobic photooxidation process with a continuous-flow microreactor that can form a slug flow region on the chip. The approach solved several problems raised by using batch systems.
Keywords: oxygen; photooxidation; green chemistry; microreactor; slug flow